(untitled) (Libellarium: journal for research in the field of information and related sciences, 2016)
The paper presents the findings of the City and University Library in Osijek research on the communication knowledge and skills required for the good communication between the library and its customers. Assertive communication is described as a means that can contribute to the positive perception of a library as an institution. The paper discusses the need for the librarians to acquire good communication skills in order to present the library and the array of its services (projects, departments, etc.) in the best possible way to the public. This argument is supported by the findings of the web survey conducted via the library’s Facebook page in 2012. The survey evaluated the communication skills of the librarians working in the City and University Library with the main goal of detecting problems in communication with library customers and ensure the high quality communication and service in the future.